The Impact of Abusive Supervision on Employees' Attitude: Moderating Role of Islamic Work Ethics (Journal of Asian Development Studies, 2025)
This study tries to examine the impact of abusive supervision on employee outcomes, which are emotional exhaustion, organisational commitment, and job satisfaction. Further, this study examines the moderating role of Islamic work ethics on the relationship between abusive supervision and work outcomes. In this study, data were collected from 270 respondents, comprising both male and female employees from the healthcare sector in Pakistan. The targeted population was Rawalpindi and Islamabad. This study found that abusive supervision has a significant positive relationship with emotional exhaustion, whereas it has a significant negative relationship with organisational commitment and job satisfaction. The study found the moderating support for Islamic work ethics between abusive supervision and emotional exhaustion. Limitations, future directions, and managerial implications are also mentioned.